Pengaruh Kepemimpinan Situasional dan Budaya Kerja terhadap Prestasi Kerja - Amalia Amalia; A Nubahriati; Andi Muhammad Fara Kessi (Pascasarjana STIE Amkop Makassar, 2022)
The aims of this research are: (i). to identify and analyze the direct influence of situational leadership on work performance; (ii). to determine and analyze the direct influence of work culture on work performance; (iii) to determine and analyze the simultaneous influence of situational leadership and work culture on work performance.This research is located at the Department of Housing and Settlement Areas of West Sulawesi Province, using a survey method with a sample of 44 respondents. Data were analyzed using multiple regression, t test and determination test.The results showed that: (i). Situational leadership directly affects work performance; (ii). Work culture directly affects work performance; (iii). Directly and simultaneously situational leadership and work culture affect work performance. Keywords: Situational Leadership; Work Culture; Work performance